Efeitos da administração crônica da digoxina e do verapamil sobre o desempenho físico e a estrutura e função cardíaca em ratos submetidos ao treinamento físico intervalado - Neves, Claodete Hasselstrom (2015)
The aim of this study was to investigate the effects of chronic administration of cardiotonic (digoxin) and the calcium channel blocker (verapamil) during high-intensity interval exercise training (IET) on physical performance, functional capacity and cardiac morphology of rats. For this study, 48 Wistar rats, 60 days old, were randomly distributed into 6 groups (N = 8 / group): control, untrained (C), trained without drug administration (T), digoxin untrained (DIGO), verapamil without training (VERA), trained with digoxin administration (TDIGO) and trained with verapamil administration (TVERA). Digoxin and verapamil were administered by gavage at a dose of 30μg/kg/day and 5.0 mg.kg-1, respectively, throughout the experimental period. The groups T, TDIGO and TVERA underwent a IET program on a treadmill for 60 days. The progressive maximal exercise test was applied (TPM) and determined the serum concentration of lactate (LAC) blood. The IET consisted of sessions running on a treadmill 1 h/day, 5 days/week for 60 days. The training intensity was 80% of the maximum velocity (Vmax) achieved in the stress test before the TAI for 8 min and 20% of Vmax for 2 min. Cardiac function was assessed by echocardiography. Was collected skeletal muscle, cardiac muscle and total body fat (TBF) for anatomical data, the left ventricle (LV) for histological analysis and blood for biochemical analysis. The comparison between groups was performed using analysis of variance (ANOVA) or Kruskal Wallis for the two independent factors, complemented by the Bonferroni test, Tukey or Dunn. The significance level considered was 5%. The ratio VE final body weight (FBW), LV diastolic diameter (LVDD) and LV systolic diameter (LVSD) were higher in TDIGO group than the group T and DIGO. The parameters MET were higher and the concentration of LAC was lower in rats training in relation to the untrained. The relationship GOR/FBW was lower in TDIGO and TVERA compared to DIGO and VERA respectively. The ratio VE/FBW was higher in TVERA compared to VERA. The of the LV inside diameter (LVID) T group, TDIGO and TVERA were higher compared to C, TDIGO had increased compared to DIGO. Total cholesterol and LDL were higher in TDIGO compared to DIGO. The area of cardiomyocytes was higher in VERA and T compared to group C. Conclusion: TAI induced cardiac hypertrophy of the eccentric type. However, concomitant administration of digoxin or verapamil did not affect the cardiac morphology, cardiac function and physical performance in rats submitted to training.